The Influence of Future Orientation, Self-Control, and Financial Responsibility on Financial Management Behavior: A Comparative Study Between Married and Unmarried Women - Marsya Lydia Putri; Rosmida Rosmida (Majapahit Journal of Islamic Finance and Management, 2025)
This study was carried out to examine psychological factors influencing women’s financial management behavior, including both married and unmarried individuals. This research aims to analyze the effects of Future Orientation (X1), Self-Control (X2), and Financial Responsibility (X3) on Financial Management Behavior (Y), as well as to compare their impacts between the two groups of women. The method used was a quantitative comparative explanatory with 100 respondents in Bengkalis District, Riau, who were chosen using a purposive sampling technique. Data analysis was performed using SEM-PLS along with Multi-Group Analysis (MGA). The findings indicate that Future Orientation (β = 0.209), Self-Control (β = 0.220), and Financial Responsibility (β = 0.435) positively and significantly influence Financial Management Behavior, with Financial Responsibility being the strongest contributing variable. The results of the MGA test reveal no significant differences in financial management behavior between married and unmarried women (p-value > 0.05). Based on these results, it is recommended that financial literacy programs, personal financial management training, and financial behavior improvement interventions be focused on strengthening future orientation, self-control, and financial responsibility. Educational institutions, financial institutions, and women's communities are advised to provide continuous education so that all women, regardless of marital status, are able to build healthier and more sustainable financial behaviors.